2021
DOI: 10.3390/s21124131
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Nanocomposite-Modified Electrochemical Sensors for Water Quality Monitoring

Abstract: Electrochemical sensors play a significant role in detecting chemical ions, molecules, and pathogens in water and other applications. These sensors are sensitive, portable, fast, inexpensive, and suitable for online and in-situ measurements compared to other methods. They can provide the detection for any compound that can undergo certain transformations within a potential window. It enables applications in multiple ion detection, mainly since these sensors are primarily non-specific. In this paper, we provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 299 publications
1
44
0
Order By: Relevance
“…2 ) is one of the most common inorganic nitrogenous compounds found in the environment and is widely used as a food additive and preservative [1], as well as nitrogenbased fertilizers utilized in agriculture [2,3]. Nonetheless, nitrite has been classified as a hazardous species due to its toxicity to humans.…”
Section: Introductionmentioning
confidence: 99%
“…2 ) is one of the most common inorganic nitrogenous compounds found in the environment and is widely used as a food additive and preservative [1], as well as nitrogenbased fertilizers utilized in agriculture [2,3]. Nonetheless, nitrite has been classified as a hazardous species due to its toxicity to humans.…”
Section: Introductionmentioning
confidence: 99%
“…To date, various electrochemical sensing techniques have been designed for the detection of toxic amounts of pesticide residues from the environment or agricultural products. 2 5 These methods have emerged as potential alternates for traditional detection techniques which are considered as time-consuming, expensive, laborious, requiring highly trained persons to operate the highly sophisticated instruments, and are limited in centralized laboratories such as mass spectrometry (MS), liquid chromatography–MS, gas chromatography–MS, HPLC, electrophoresis, and so forth owing to their inexpensiveness, rapidity, lack of sample pretreatment steps, simple design, easy handling, and feasibility of on-site detection of pesticides. 6 , 7 The electrochemical methods have usually based on targeting a nervous system enzyme acetylcholinesterase (AChE), which is inhibited by the action of OP and CB pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of precise and rapid techniques for the sensitive detection of pesticide residues from air, food, or water is an important focus of modern research to ensure food safety. To date, various electrochemical sensing techniques have been designed for the detection of toxic amounts of pesticide residues from the environment or agricultural products. These methods have emerged as potential alternates for traditional detection techniques which are considered as time-consuming, expensive, laborious, requiring highly trained persons to operate the highly sophisticated instruments, and are limited in centralized laboratories such as mass spectrometry (MS), liquid chromatography–MS, gas chromatography–MS, HPLC, electrophoresis, and so forth owing to their inexpensiveness, rapidity, lack of sample pretreatment steps, simple design, easy handling, and feasibility of on-site detection of pesticides. , The electrochemical methods have usually based on targeting a nervous system enzyme acetylcholinesterase (AChE), which is inhibited by the action of OP and CB pesticides. The enzyme-based electrochemical biosensors can be reliable tools for on-site monitoring of pesticides if they could be miniaturized in the form of a portable measuring device. However, the use of enzymes is critical because of its low stability, storage requirements, and optimum conditions such as pH, temperature, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Three reviews point out the role of electrochemical sensors for water quality monitoring [ 2 ] with nanostructured highly sensing layers. It has been demonstrated that polymer imprinting technology enhances selectivity of the electrochemical and impedimetric sensors of metal ions, Cr(VI), pesticides, and bacteria [ 2 , 3 , 4 ].…”
mentioning
confidence: 99%
“…Three reviews point out the role of electrochemical sensors for water quality monitoring [ 2 ] with nanostructured highly sensing layers. It has been demonstrated that polymer imprinting technology enhances selectivity of the electrochemical and impedimetric sensors of metal ions, Cr(VI), pesticides, and bacteria [ 2 , 3 , 4 ]. In the domain of electrochemical sensors, much hope is now placed on carbon paste electrodes (CPEs) for their ease of preparation, high surface area, and versatility.…”
mentioning
confidence: 99%